Performance Assesment Analysis Of Beef Supplier Using AHP and TOPSIS in UMKM Paramuda Olahan Jaya - Rafqi Gilang Perdana (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
UMKM Paramuda Olahan Jaya is a business engaged in food processing of beef raw materials. So far, the business has collaborated with 6 permanent suppliers but there is a problem of rejected goods on the receipt of beef raw materials so that it disrupts the production process. The purpose of this study is to assess performance based on 5 criteria and 10 selected sub-criteria so as to get alternative proposals for indicators of purchasing raw materials and potential suppliers. The methods used by researchers in conducting performance assessments are AHP (Analytical Hierarchy Proces) and TOPSIS (Technique for Order Performance by Ideal Similarity). The results of data processing analysis using the AHP method show that there are 5 criteria that the quality criteria get the largest weight of 0.28 (28%) and 10 sub-criteria that the quality consistency of specification conformity has the largest weight of 0.51 (51%), while the results of the TOPSIS method calculation produce a solutive preference value for alternative suppliers, namely Kapita Meat getting the highest result of 0.67. Then the calculation results become a proposal in choosing the best purchasing process indicators and supplier performance.